LGG-07. CLINICAL FEATURES OF NON-CANONICAL MOLECULAR DRIVERS IN PLGG; AN UPDATE FORM THE INTERNATIONAL PLGG TASKFORCE. (23rd April 2019) - Ryall, Scott; Zapotocky, Michal; Fukuoka, Kohei; Guerreiro-Stucklin, Ana; Bennett, Julie; Arnoldo, Anthony; Kowalski, Paul; Johnson, Monique; Nobre, Liana Figueiredo; Lassaletta, Alvaro; Bouffet, Eric; Bartels, Ute; et al.
Abstract: Molecular characterization of pediatric low-grade gliomas (pLGG) have identified recurrent alterations, most commonly involving BRAF and NF1, which have been exploited to aid in diagnosis and treatment decisions. However, a significant portion do not have these canonical alterations, and the genetics and clinical course of these tumors remains unknown. We molecularly characterized a cohort of 986 patients diagnosed at SickKids from 1990–2017 with comprehensive long-term clinical data. For the rare non-canonical alterations uncovered, data was supplemented with cases from the Taskforce. Within the SickKids cohort, 72% were driven by canonical alterations in either BRAF (38% fusions, 16% V600E) or NF1 (18%). 11.5% were driven via recurrent non-canonical events involving FGFR1 (6%), FGFR2 (1%), MYB (1%), MYBL1 (1%), H3F3A (2%) or IDH1 (0.5%). The Taskforce supplemented cohort revealed that most FGFR1/2 fusions (n=51) were hemispheric and benign, with no deaths observed. In contrast, FGFR1 activating mutations (n=29) were commonly observed as a second hit, occurred throughout the neuraxis, and at an older age. These tumors were more aggressive, having a poor response to therapy and resulting in death. MYB/MYBL1 alterations (n=19) were seen exclusively in angiocentric gliomas and diffuse astrocytomas, respectively. Both are primarily hemispheric and often occur as massive lesions in childhood, yet have excellent long-term outcome. IDH1 (n=8) was seen mostly in adolescents (15–18 years). Importantly, several had a long history of seizures and presented with small lesions years prior to surgery. While all tumours eventually progressed, some (n=6) are alive up to 13 years post diagnosis. H3F3A driven pLGGs (n=12) progressed early, (median 11 months) and all patients succumbed to their disease. The work here represents the largest cohort of non-canonical pLGGs assembled. Our work supports a diagnostic workflow which includes these alterations, and we provide preliminary clinical features of these tumors to better equip practicing clinicians.